Dynamic Pricing in Movie Tickets using Regression Techniques - Gupta V.; Singh K.; Arjaria S.K.; Biswas B. (My University, 2025)
In this work, we developed a hybrid model using data clustering and regression techniques to introduce a dynamic pricing scheme for booking online movie tickets. The model is based on different types of uncertainties in the given scenario. We study the performance of our model on four different regression techniques to maximize revenue generation. © 2018 IEEE.